Structural basis for allosteric modulation of class B GPCRs - Wootten, Denise (Annu Rev Pharmacol Toxicol, 2019)
Recent advances in our understanding of the structure and function of class B GPCRs provide multiple opportunities for targeted development of allosteric modulators. Given the pleiotrophic signaling patterns emanating from these receptors in response to a variety of natural agonist ligands, modulators have the potential to sculpt the responses to meet distinct needs of different groups of patients. In this review, we provide insights into how this family of GPCRs differs from the rest of this superfamily, how orthosteric agonists bind and activate these receptors, the potential for allosteric modulators to interact with various regions of these targets, and the allosteric influence of endogenous proteins on the pharmacology of these receptors that are important considerations when developing new therapies.